2012
DOI: 10.3354/cr01127
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal, seasonal, and altitudinal trends in microclimate across a tropical montane cloud forest

Abstract: Altitudinal gradients are often used as natural laboratories to study ecosystem dynamics, biodiversity, and species' distribution response to climate gradients. However, the underlying climate gradients are rarely described in detail, especially in the tropics. In this study, we describe the diurnal and seasonal patterns in microclimate across a 3900 m altitudinal gradient in and adjacent to the Kosñipata Valley in Manu National Park, Peru, on the eastern slope of the tropical Andes. We focus on the understudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(123 citation statements)
references
References 56 publications
3
119
1
Order By: Relevance
“…The soils at higher elevations are shallower to bedrock but have deeper organic horizons ( Table 2). Further information on the sites and descriptions of the soils (Quesada et al 2010), climate (Rapp and Silman 2012), above-ground productivity and floristic composition (Asner et al 2014;Feeley et al 2011;Girardin et al 2010) are reported elsewhere.…”
Section: Study Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…The soils at higher elevations are shallower to bedrock but have deeper organic horizons ( Table 2). Further information on the sites and descriptions of the soils (Quesada et al 2010), climate (Rapp and Silman 2012), above-ground productivity and floristic composition (Asner et al 2014;Feeley et al 2011;Girardin et al 2010) are reported elsewhere.…”
Section: Study Sitesmentioning
confidence: 99%
“…Because December falls in the early wet season for all study sites, soil microbes were not water limited during sample collection (Rapp and Silman 2012). For each sub-plot, soil was removed from a 40 9 40 cm area to 10 cm depth from the organic horizon.…”
Section: Soil Sampling and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further descriptions of soil properties (Quesada et al 2010;Whitaker et al 2014;Zimmermann et al 2009), climate (Rapp and Silman 2012) and aboveground productivity and floristic composition (Asner et al 2013;Feeley et al 2011;Girardin et al 2010) for these sites are reported elsewhere.…”
Section: Study Sitesmentioning
confidence: 99%
“…Epiphytic vegetation tends to be more numerous in sites with frequent fog occurrence, because it depends strongly on the humidity provided by the fog (Mondragón, Valverde, & Hernández‐Apolinar, ). Given that the frequency of fog occurrence usually increases with altitude (Pryet et al, ; Rapp & Silman, ), it is probable that epiphyte load shows a similar tendency (cf. Bruijnzeel et al, ).…”
Section: Discussionmentioning
confidence: 99%